Legalitas Agama (Tahaqquq Al-Adyân) Perspektif Ibn ‘Arabî - Mukhlis Mukhlis (Ulumuna, 2006)
Ibn ‘Arabî is one of the prominent and authoritative thinkers on Islamic mysticisms. Among his starting and brilliant ideas is the unity of religions (wahdah al-adyân), one of the fundamental ideas of religious pluralism. The supporters of pluralism expose his opinion on the unity of religions intensely and consider any religions valid and true. This article examines further Ibn ‘Arabî’s thought on pluralism. Through critical analysis on his works, I find that positioning his thought on pluralism issue is a partial understanding of his complete views on such topic. The unity of religions as described by Ibn ‘Arabî is a system of belief which is closely related to the Prophetical tradition and not merely based on the speculative assumption of human-being. He formulated a parameter—to see whether a religion is true or not—which contains three principal dimentions: the divinity, prophecy, and devotion.